Dynamic capital structure with callable debt and debt renegotiations - Christensen, Peter Ove; Flor, Christian Riis; Lando, David; Miltersen, Kristian R. (Journal of Corporate Finance, 2014)
We consider a dynamic trade-off model of a firm's capital structure with debt renegotiation. Debt holders only accept restructuring offers from equity holders backed by threats which are in the equity holders' own interest to execute. Our model shows that in a complete information model in which taxes and bankruptcy costs are the only frictions, violations of the absolute priority rule (APR) are typically optimal. The size of the bankruptcy costs and the equity holders' bargaining power affect the size of APR violations, but they have only a minor impact on the choice of capital structure.